Do Euro Area Countries Respond Asymmetrically to the Common Monetary Policy?1. (23rd June 2013) - Barigozzi, Matteo; Conti, Antonio M.; Luciani, Matteo
Abstract We investigate the possible existence of asymmetries among Euro Area countries reactions to the European Central Bank monetary policy. Our analysis is based on a Structural Dynamic Factor model estimated on a large panel of Euro Area quarterly variables. Although the introduction of the euro has changed the monetary transmission mechanism in the individual countries towards a more homogeneous response, we find that differences still remain between North and South Europe in terms of prices and unemployment. These results are the consequence of country‐specific structures, rather than of European Central Bank policies.